Facial acupuncture as a way to restore external and internal well-being (Journal of Face Aesthetics, 2024)
Facial acupuncture is non‑invasive and safe, and it can significantly improve skin elasticity by stimulating collagen production and enhancing blood circulation. This leads to reduction in wrinkles, improvement in muscle tone, and skin tightening. Acupuncture can help alleviate inflammatory skin conditions like acne or psoriasis by regulating hormonal function and the immune system. Additionally, it can bring mental health benefits by reducing stress and enhancing overall well‑being, potentially boosting self‑confidence and self‑acceptance. Ultimately, facial acupuncture represents a holistic approach to health and beauty, focusing not only on enhancing external appearance but also on balancing the internal energy of the body, which can have a positive impact on quality of life.
Keywords: pathophysiognomics; facial aesthetics; acupuncture